Polarizing film, laminated polarizing film, image display panel, and image display device
Patent Information
- Application Number
- JP2021044401
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-30
- Filing Date
- 2021-03-18
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-03-18
AI Technical Summary
Polarizing films used in image display devices face issues of thermal contraction and expansion, leading to cracks and reduced flexibility due to differing shrinkage forces in different directions, especially in high-temperature environments, and the demand for higher durability in harsh conditions.
A polarizing film with a transparent protective film laminated on one or both sides, containing a water-soluble radical scavenger, maintains mechanical strength by suppressing polyene formation and transverse cracks, with a length ratio of 2.0 ≤ a/b, where a represents the length parallel to the absorption axis and b is perpendicular to it, and a value greater than 200.
The film effectively suppresses transverse cracks and maintains mechanical strength in high-temperature environments, enhancing durability and flexibility.
Abstract
Description
[Technology Field]
[0001] The present invention relates to a polarizing film, a laminated polarizing film, an image display panel, and an image display device. [Background technology]
[0002] Conventionally, polyvinyl alcohol-based films that have been dyed (containing dichroic substances such as iodine or dichroic dyes) have been used as polarizing films for various image display devices such as liquid crystal displays and organic EL displays, because they possess both high transmittance and high polarization. These polarizing films are manufactured by subjecting a polyvinyl alcohol-based film to various treatments in a bath, such as swelling, dyeing, crosslinking, and stretching, followed by a washing treatment and then drying. Furthermore, these polarizing films are usually used as polarizing films (polarizing plates) to which a protective film such as triacetylcellulose is bonded using an adhesive to one or both sides.
[0003] The polarizing film may be laminated with other optical layers as needed to form a laminated polarizing film (optical laminate). The polarizing film or the laminated polarizing film (optical laminate) is then bonded between an image display cell such as a liquid crystal cell or an organic EL element and a front transparent member such as a front transparent plate (window layer) or a touch panel on the viewing side via an adhesive layer or bonding agent, and used as one of the various image display devices (Patent Document 1).
[0004] In recent years, the applications of such various image display devices have expanded beyond mobile devices such as mobile phones and tablet terminals to include in-vehicle image display devices such as car navigation systems and rearview monitors. Accordingly, the polarizing films and laminated polarizing films are required to have higher durability under harsher environments (for example, high-temperature environments) than previously required, and polarizing films and image display devices aimed at ensuring such durability have been proposed (Patent Documents 2-3). [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2014-102353 [Patent Document 2] Special Publication No. 2012-516468 [Patent Document 3] Japanese Patent Publication No. 2018-101117 [Overview of the Initiative] [Problems that the invention aims to solve]
[0006] The polarizing films or laminated polarizing films (optical laminates) described above have a problem in that cracks can form in the polarizing film when exposed to high-temperature environments because the degree of thermal contraction and / or thermal expansion differs for each component that makes them up. In addition, as polyene formation occurs and grows in the polarizing film, the intermolecular interactions of polyvinyl alcohol decrease, leading to a deterioration of flexibility.
[0007] On the other hand, the market demands polarizing films with a certain ratio of the length parallel to the absorption axis to the length perpendicular to the absorption axis (polarizing films with a high aspect ratio) from the perspective of design in the interior space of a vehicle. Generally, the shrinkage force in the stretching direction (MD) of a polarizing film is greater than that in the direction perpendicular to the stretching direction (TD). Moreover, polarizing films with such a length ratio usually have a greater shrinkage force for a given width in the MD direction of the polarizing film than in the TD direction of the polarizing film. Therefore, it has been found that when exposed to high-temperature environments, polarizing films with reduced flexibility cannot withstand the shrinkage force in the MD direction (the direction parallel to the absorption axis of the polarizing film), and are prone to developing transverse cracks (orthogonal cracks) parallel to the absorption axis of the polarizing film.
[0008] In view of the above circumstances, the present invention aims to provide a polarizing film having a high aspect ratio that is excellent in suppressing the occurrence of transverse cracks in a direction parallel to the absorption axis of the polarizing film in a high-temperature environment.
[0009] Furthermore, the present invention aims to provide a laminated polarizing film using the above-mentioned polarizing film, an image display panel, and an image display device. [Means for solving the problem]
[0010] In other words, the present invention relates to a polarizing film in which a transparent protective film is laminated to one or both sides of a polarizing film, wherein the polarizing film contains a water-soluble radical scavenger and satisfies the condition of the ratio of lengths represented by the general formula (X): 2.0 ≤ a / b (wherein the general formula (X), a represents the length (mm) parallel to the absorption axis of the polarizing film and is greater than 200, and b represents the length (mm) perpendicular to the absorption axis of the polarizing film).
[0011] Furthermore, the present invention relates to a laminated polarizing film in which the polarizing film is bonded to an optical layer.
[0012] Furthermore, the present invention relates to an image display panel in which the polarizing film or the laminated polarizing film is bonded to an image display cell.
[0013] Furthermore, the present invention relates to an image display device comprising a front transparent member on the polarizing film or laminated polarizing film side of the image display panel. [Effects of the Invention]
[0014] While the detailed mechanism of action of the polarizing film of the present invention remains unclear, it is presumed to be as follows. However, the present invention does not have to be interpreted as being limited to this mechanism of action.
[0015] The polarizing film of the present invention has a transparent protective film laminated on one or both sides of a polarizing film. The polarizing film contains a water-soluble radical scavenger and satisfies the condition of the ratio of lengths represented by the general formula (X): 2.0 ≤ a / b (in the general formula (X), a represents the length (mm) parallel to the absorption axis of the polarizing film and is a value exceeding 200, and b represents the length (mm) perpendicular to the absorption axis of the polarizing film).) Since the water-soluble radical scavenger can suppress the polyene formation of the polarizing film in a high-temperature environment, the mechanical strength of the polarizing film can be maintained. Therefore, in a polarizing film (a polarizing film having a high aspect ratio) in which the ratio of the length parallel to the absorption axis of the polarizing film is a certain value or more with respect to the length perpendicular to the absorption axis of the polarizing film, the effect of suppressing the generation of transverse cracks in the parallel direction with respect to the absorption axis of the polarizing film is excellent.
[0016] In addition, since the polarizing film of the present invention contains the above-mentioned water-soluble radical scavenger, it can capture radicals that may be generated due to the progress of polyene formation of the polarizing film. Therefore, in a high-temperature environment, the effect of suppressing the decrease in the single transmittance of the polarizing film is also excellent.
Embodiments for Carrying Out the Invention
[0017] <Polarizing Film> The polarizing film of the present invention has a transparent protective film laminated on one or both sides of a polarizing film.
[0018] <Polarizing Film> The polarizing film is formed by adsorbing and orienting a dichroic substance such as iodine or a dichroic dye on a polyvinyl alcohol-based film. From the viewpoint of the initial polarization performance of the polarizing film, iodine is preferable as the dichroic substance.
[0019] The polyvinyl alcohol (PVA)-based film has light transmittance in the visible light region, and those that disperse and adsorb dichroic substances such as iodine and dichroic dyes can be used without particular limitation. Usually, the PVA-based film used as a raw web preferably has a thickness of about 1 to 100 μm, more preferably about 1 to 50 μm, and a width of about 100 to 5000 mm.
[0020] Examples of materials for the polyvinyl alcohol-based film include polyvinyl alcohol or its derivatives. Examples of polyvinyl alcohol derivatives include polyvinyl formal, polyvinyl acetal; olefins such as ethylene and propylene; unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid, and those modified with their alkyl esters, acrylamide, etc. The polyvinyl alcohol preferably has an average degree of polymerization of about 100 to 10,000, more preferably about 1,000 to 10,000, and even more preferably about 1,500 to 4,500. Furthermore, the polyvinyl alcohol preferably has a degree of saponification of about 80 to 100 mol%, more preferably about 95 mol% to 99.95 mol. The average degree of polymerization and the degree of saponification can be determined in accordance with JIS K 6726.
[0021] The polyvinyl alcohol-based film may contain additives such as plasticizers and surfactants. Examples of plasticizers include polyols and their condensates, such as glycerin, diglycerin, triglycerin, ethylene glycol, propylene glycol, and polyethylene glycol. There are no particular restrictions on the amount of additives used, but for example, about 20% by weight or less in the polyvinyl alcohol-based film is preferred.
[0022] If the polarizing film contains iodine as the dichroic substance, it is preferable that the iodine content is 1% by weight or more and 20% by weight or less. From the viewpoint of suppressing color fading during durability testing, the iodine content of the polarizing film is preferably 1.5% by weight or more, more preferably 2% by weight or more, and from the viewpoint of preventing polyene formation, it is preferably 12% by weight or less, and more preferably 10% by weight or less.
[0023] The polarizing film contains a water-soluble radical scavenger. The water-soluble radical scavenger may be used alone or in combination of two or more types. From the viewpoint of being able to efficiently permeate the polarizing film together with water during the production of the polarizing film, being able to impregnate the polarizing film at a high concentration, and being able to impregnate even a thick polyvinyl alcohol-based film in a short time and thereby increase the productivity of the polarizing film, the water-soluble radical scavenger is preferably a compound that can dissolve in 1 part by weight or more per 100 parts by weight of water at 25°C, more preferably a compound that can dissolve in 2 parts by weight or more per 100 parts by weight of water at 25°C, and even more preferably a compound that can dissolve in 5 parts by weight or more per 100 parts by weight of water at 25°C.
[0024] The aforementioned water-soluble radical scavenger is presumed to be able to suppress polyene formation of the polarizing film under high-temperature conditions. Examples of the water-soluble radical scavenger include compounds having radical scavenging function, such as hindered phenol, hindered amine, phosphorus, sulfur, benzotriazole, benzophenone, hydroxylamine, salicylic acid ester, and triazine compounds. From the viewpoint of the radical species generated in the polarizing film, the water-soluble radical scavenger is preferably, for example, a nitroxy radical or a compound having a nitroxide group.
[0025] As for the nitroxy radical or compound having a nitroxide group, from the viewpoint of having a radical that is relatively stable at room temperature and in air, N-oxyl compounds (with CN(-C)-O as a functional group) are selected. · Compounds having (O · Examples of N-oxyl compounds include those that exhibit an oxy radical, and known ones can be used. Examples of N-oxyl compounds include compounds having an organic group with the following structure. [Formula 1] (In general formula (1), R 1 R represents an oxyradical. 2 From R 5independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and n represents 0 or 1. In the general formula (1), the left side of the dotted line represents an arbitrary organic group.
[0026] Examples of the compound having the above organic group include compounds represented by the following general formulas (2) to (5).
Chemical Formula 2
Chemical Formula 3
Chemical Formula 4
Chemical Formula 5
[0027] In the above general formulas (1) to (5), R 2 to R 5From the viewpoint of availability, R is preferably an alkyl group having 1 to 6 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms. Also, in the general formula (2) above, from the viewpoint of availability, 6 R is preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom. Also, in the above general formula (3), R is preferred from the viewpoint of availability. 7 and R 8 R is preferably independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom. Also, in the above general formula (4), R is preferred from the viewpoint of availability. 9 From R 11 It is preferable that R is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. Also, in the above general formula (5), from the viewpoint of availability, 12 It is preferable that n is a hydroxyl group, an amino group, or an alkoxy group. In the above general formulas (1) to (5), n is preferably 1 from the viewpoint of availability.
[0028] Furthermore, examples of the N-oxyl compounds include those described in Japanese Patent Publication No. 2003-64022, Japanese Patent Publication No. 11-222462, Japanese Patent Publication No. 2002-284737, and International Publication No. 2016 / 047655.
[0029] Examples of compounds having a nitroxy radical or a nitroxide group include the following compounds. [C6] (In general formula (6), R represents a hydrogen atom, or an alkyl group, acyl group, or aryl group having 1 to 10 carbon atoms.) [C7] [C8]
[0030] Furthermore, from the viewpoint of suppressing polyene formation of the polarizing film under high-temperature conditions, the water-soluble radical scavenger preferably has a molecular weight of 1000 or less, more preferably 500 or less, and even more preferably 300 or less.
[0031] The polarizing film preferably contains 20% by weight or less of the water-soluble radical scavenger. The polarizing film preferably contains 0.005% by weight or more of the water-soluble radical scavenger, more preferably 0.01% by weight or more, even more preferably 0.02% by weight or more, and more preferably 15% by weight or less, more preferably 12% by weight or less, and even more preferably 10% by weight or less, from the viewpoint of suppressing polyene formation of the polarizing film in a high-temperature environment.
[0032] The polarizing film satisfies the length ratio condition expressed by the general formula (X): 2.0 ≤ a / b (wherein general formula (X), a represents the length (mm) of the polarizing film parallel to the absorption axis and is greater than 200, and b represents the length (mm) of the polarizing film perpendicular to the absorption axis). The term "parallel" above includes cases where the lengths are substantially parallel. Here, "substantially parallel" includes cases where the angles are 0° ± 5.0°, preferably 0° ± 3.0°, and more preferably 0° ± 1.0°. The term "perpendicular" above also includes cases where the lengths are substantially orthogonal. Here, "substantially orthogonal" includes cases where the angles are 90° ± 5.0°, preferably 90° ± 3.0°, and more preferably 90° ± 1.0°. Typically, the length ratio of the polarizing film is the same as the length ratio of the polarizing film described above.
[0033] If the a / b ratio is less than 2.0, the shrinkage force in the MD direction for a given width decreases, making it less likely for transverse cracks to occur in the polarizing film under high-temperature conditions. Furthermore, from the viewpoint of the image display size of the display in the vehicle interior, a may be 200 mm or more, preferably 250 mm or more, and from the viewpoint of shrinkage force, it may be 2000 mm or less, preferably 1500 mm or less. From the viewpoint of design in the vehicle interior, a / b is preferably 2.8 or more, and from the viewpoint of suppressing transverse cracks, it is preferably 15 or less, and more preferably 10 or less.
[0034] <Method for manufacturing polarizing film> The present invention provides a method for producing a polarizing film, which is obtained by subjecting a polyvinyl alcohol-based film to an optional swelling step and washing step, and at least a dyeing step, a crosslinking step, and a stretching step, wherein the treatment bath in one or more of the swelling step, washing step, dyeing step, crosslinking step, and stretching step contains a water-soluble radical scavenger. From the viewpoint of initial polarizing performance, an iodine-based polarizing film is preferred, and the content of the water-soluble radical scavenger and the iodine contained in the polarizing film can be controlled by the concentration of the water-soluble radical scavenger and the concentration of iodine, etc., contained in one of the treatment baths in the swelling step, dyeing step, crosslinking step, stretching step, and washing step, as well as the treatment temperature and treatment time of each treatment bath. In particular, when a washing process is performed after a dyeing process, a crosslinking process, and a stretching process, the washing process can be easily adjusted to a desired range in terms of the content of the water-soluble radical scavenger and the iodine, taking into account the processing conditions in the dyeing process, crosslinking process, and stretching process, and enabling the elution of water-soluble radical scavengers and iodine from the polyvinyl alcohol-based film or adsorption onto the polyvinyl alcohol-based film.
[0035] Furthermore, each treatment bath in the swelling step, dyeing step, crosslinking step, stretching step, and washing step may contain additives such as zinc salts, pH adjusters, pH buffers, and other salts. Examples of zinc salts include zinc halides such as zinc chloride and zinc iodide; and inorganic zinc salts such as zinc sulfate and zinc acetate. Examples of pH adjusters include strong acids such as hydrochloric acid, sulfuric acid, and nitric acid, and strong bases such as sodium hydroxide and potassium hydroxide. Examples of pH buffers include carboxylic acids and their salts such as acetic acid, oxalic acid, and citric acid, and inorganic weak acids and their salts such as phosphoric acid and carbonic acid. Examples of other salts include chlorides such as sodium chloride, potassium chloride, and barium chloride; nitrates such as sodium nitrate and potassium nitrate; sulfates such as sodium sulfate and potassium sulfate; and salts of alkali metals and alkaline earth metals.
[0036] The concentration of the water-soluble radical scavenger compound contained in any of the aforementioned treatment baths cannot be determined in general terms because it is affected by the number of treatments, treatment time, treatment temperature, etc. for each treatment. However, from the viewpoint of efficiently controlling the content of the water-soluble radical scavenger in the polarizing film, it is generally preferable to have a concentration of 0.01% by weight or more, more preferably 0.05% by weight or more, even more preferably 0.1% by weight or more, and preferably 30% by weight or less, more preferably 25% by weight or less, and even more preferably 20% by weight or less.
[0037] The swelling step involves immersing a polyvinyl alcohol-based film in a swelling bath. This step removes dirt and blocking agents from the surface of the polyvinyl alcohol-based film and suppresses uneven dyeing by swelling the film. The swelling bath typically uses a water-based medium such as water, distilled water, or pure water. The swelling bath may also contain surfactants, alcohol, etc., as appropriate, according to conventional methods.
[0038] The temperature of the swelling bath is preferably about 10 to 60°C, more preferably about 15 to 45°C, and even more preferably about 18 to 30°C. The immersion time in the swelling bath cannot be determined definitively because the degree of swelling of the polyvinyl alcohol-based film is affected by the temperature of the swelling bath, but it is preferably about 5 to 300 seconds, more preferably about 10 to 200 seconds, and even more preferably about 20 to 100 seconds. The swelling process may be performed only once, or multiple times as necessary.
[0039] The dyeing step involves immersing a polyvinyl alcohol-based film in a dyeing bath (iodine solution), which allows iodine to be adsorbed and oriented on the polyvinyl alcohol-based film. The iodine solution is preferably an aqueous iodine solution and contains iodine and an iodide as a solubilizing agent. Examples of iodides include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. Among these, potassium iodide is preferred from the viewpoint of controlling the potassium content in the polarizing film.
[0040] In the staining bath, the concentration of iodine is preferably about 0.01 to 1% by weight, and more preferably about 0.02 to 0.5% by weight. In the staining bath, the concentration of iodide is preferably about 0.01 to 20% by weight, more preferably about 0.05 to 10% by weight, and even more preferably about 0.1 to 5% by weight.
[0041] The temperature of the dyeing bath is preferably about 10 to 50°C, more preferably about 15 to 45°C, and even more preferably about 18 to 30°C. The immersion time in the dyeing bath cannot be determined definitively because the degree of dyeing of the polyvinyl alcohol-based film is affected by the temperature of the dyeing bath, but it is preferably about 10 to 300 seconds, and more preferably about 20 to 240 seconds. The dyeing process may be performed only once, or multiple times as necessary.
[0042] The crosslinking step involves immersing a polyvinyl alcohol-based film in a treatment bath (crosslinking bath) containing a boron compound. The boron compound crosslinks the polyvinyl alcohol-based film, allowing iodine molecules or dye molecules to be adsorbed onto the crosslinked structure. Examples of the boron compound include boric acid, borate salts, and borax. The crosslinking bath is generally an aqueous solution, but may also be a mixed solution of a water-miscible organic solvent and water. Furthermore, the crosslinking bath may contain potassium iodide to control the potassium content in the polarizing film.
[0043] In the crosslinking bath, the concentration of the boron compound is preferably about 1 to 15% by weight, more preferably about 1.5 to 10% by weight, and even more preferably about 2 to 5% by weight. Furthermore, when potassium iodide is used in the crosslinking bath, the concentration of potassium iodide in the crosslinking bath is preferably about 1 to 15% by weight, more preferably about 1.5 to 10% by weight, and even more preferably about 2 to 5% by weight.
[0044] The temperature of the crosslinking bath is preferably around 20 to 70°C, and more preferably around 30 to 60°C. The immersion time in the crosslinking bath cannot be determined definitively because the degree of crosslinking of the polyvinyl alcohol-based film is affected by the temperature of the crosslinking bath, but it is preferably around 5 to 300 seconds, and more preferably around 10 to 200 seconds. The crosslinking process may be performed only once, or multiple times as necessary.
[0045] The stretching step is a process of stretching a polyvinyl alcohol-based film to a predetermined magnification in at least one direction. Generally, the polyvinyl alcohol-based film is uniaxially stretched in the transport direction (longitudinal direction). The stretching method is not particularly limited, and either wet stretching or dry stretching can be used. The stretching step may be performed only once, or multiple times as necessary. The stretching step may be performed at any stage in the production of a polarizing film.
[0046] In the wet stretching method, the treatment bath (stretching bath) can usually be a solvent such as water or a mixed solution of a water-miscible organic solvent and water. The stretching bath may contain potassium iodide from the viewpoint of controlling the potassium content in the polarizing film. When potassium iodide is used in the stretching bath, the concentration of potassium iodide in the stretching bath is preferably about 1 to 15% by weight, more preferably about 2 to 10% by weight, and more preferably about 3 to 6% by weight. Furthermore, the treatment bath (stretching bath) may contain the boron compound from the viewpoint of suppressing film breakage during stretching. In this case, the concentration of the boron compound in the stretching bath is preferably about 1 to 15% by weight, more preferably about 1.5 to 10% by weight, and more preferably about 2 to 5% by weight.
[0047] The temperature of the stretching bath is preferably around 25 to 80°C, more preferably around 40 to 75°C, and even more preferably around 50 to 70°C. The immersion time in the stretching bath cannot be determined definitively because the degree of stretching of the polyvinyl alcohol-based film is affected by the temperature of the stretching bath, but it is preferably around 10 to 800 seconds, and more preferably around 30 to 500 seconds. The stretching treatment in the wet stretching method may be performed together with one or more of the swelling step, the dyeing step, the crosslinking step, and the washing step.
[0048] Examples of the dry stretching method include a roll stretching method, a heated roll stretching method, and a compression stretching method. The dry stretching method may be performed together with the drying process.
[0049] The total stretching ratio (cumulative stretching ratio) applied to the polyvinyl alcohol-based film can be set appropriately depending on the purpose, but is preferably about 2 to 7 times, more preferably about 3 to 6.8 times, and even more preferably about 3.5 to 6.5 times.
[0050] The cleaning step involves immersing the polyvinyl alcohol-based film in a cleaning bath, which removes any foreign matter remaining on the surface of the polyvinyl alcohol-based film. The cleaning bath typically uses a water-based medium such as water, distilled water, or pure water. Furthermore, from the viewpoint of controlling the potassium content in the polarizing film, the cleaning bath may also contain potassium iodide. In this case, the concentration of potassium iodide in the cleaning bath is preferably about 1 to 10% by weight, more preferably about 1.5 to 4% by weight, and even more preferably about 1.8 to 3.8% by weight.
[0051] The temperature of the washing bath is preferably about 5 to 50°C, more preferably about 10 to 40°C, and even more preferably about 15 to 35°C. The immersion time in the washing bath cannot be determined definitively because the degree of washing of the polyvinyl alcohol-based film is affected by the temperature of the washing bath, but it is preferably about 1 to 100 seconds, more preferably about 2 to 50 seconds, and even more preferably about 3 to 20 seconds. The swelling step may be performed only once, or multiple times as necessary.
[0052] The method for manufacturing a polarizing film of the present invention may include a drying step. The drying step is a step of drying the polyvinyl alcohol-based film that has been washed in the washing step to obtain a polarizing film, and by drying, a polarizing film having a desired moisture content can be obtained. The drying can be carried out by any suitable method, such as natural drying, forced-air drying, or heat drying.
[0053] The drying temperature is preferably around 20 to 150°C, and more preferably around 25 to 100°C. The drying time cannot be determined definitively because the degree of drying of the polarizing film is affected by the drying temperature, but it is preferably around 10 to 600 seconds, and more preferably around 30 to 300 seconds. The drying process may be performed only once, or multiple times as necessary.
[0054] The polarizing film has a thickness of approximately 1 to 50 μm, more preferably 1 to 25 μm, and even more preferably 4 to 20 μm, from the viewpoint of breaking strength and shrinkage force under high-temperature environments. In particular, to obtain a polarizing film with a thickness of 8 μm or less, the following method for manufacturing a thin polarizing film can be applied, using a laminate containing a polyvinyl alcohol-based resin layer formed on a resin substrate such as a thermoplastic resin as the polyvinyl alcohol-based film.
[0055] <Manufacturing method for polarizing films (thin polarizing films)> A method for manufacturing a polarizing film (thin polarizing film) involves the steps of: preparing a laminate by forming a polyvinyl alcohol-based resin layer containing a polyvinyl alcohol-based resin on one side of a long thermoplastic resin substrate; and, while transporting the obtained laminate in the longitudinal direction, subjecting the laminate to an arbitrary insolubilization treatment, crosslinking treatment, and washing treatment, as well as at least an air-assisted stretching treatment, a dyeing treatment, and an underwater stretching treatment, wherein the treatment bath in one or more of the insolubilization treatment, crosslinking treatment, washing treatment, dyeing treatment, and underwater stretching treatment steps contains a water-soluble radical scavenger. The content of the water-soluble radical scavenger and the iodine content contained in the polarizing film can be controlled by the concentration of the water-soluble radical scavenger, the concentration of iodine and potassium iodide, etc., contained in any of the treatment baths in the insolubilization treatment, crosslinking treatment, washing treatment, dyeing treatment, and underwater stretching treatment steps, and by the treatment temperature and treatment time of each treatment bath. In particular, when a washing process is performed, the washing process takes into account the processing conditions in the dyeing process and the underwater stretching process, and from the viewpoint that water-soluble radical scavengers and iodine can be eluted from or adsorbed onto the polyvinyl alcohol-based film, the content of the water-soluble radical scavenger and the content of the iodine can be easily adjusted to a desired range.
[0056] The concentration of the water-soluble radical scavenger contained in any of the aforementioned treatment baths cannot be determined in general terms because it is affected by the number of treatments, treatment time, treatment temperature, etc. for each treatment. However, from the viewpoint of efficiently controlling the content of hydroxyl radicals or compounds having a nitroxide group in the polarizing film, it is generally preferable to have a concentration of 0.01% by weight or more, more preferably 0.05% by weight or more, even more preferably 0.1% by weight or more, and preferably 30% by weight or less, more preferably 25% by weight or less, and even more preferably 20% by weight or less.
[0057] <Process for preparing the laminate> Any suitable method can be used to produce the laminate, for example, by applying a coating solution containing the polyvinyl alcohol-based resin (PVA-based resin) to the surface of the thermoplastic resin substrate and drying it. The thickness of the thermoplastic resin substrate is preferably about 20 to 300 μm, and more preferably about 50 to 200 μm. The thickness of the PVA-based resin layer is preferably about 3 to 40 μm, and more preferably about 3 to 20 μm.
[0058] The thermoplastic resin substrate preferably has a water absorption rate of about 0.2% or more, and more preferably about 0.3% or more, from the viewpoint of absorbing water to significantly reduce tensile stress and enable high-magnification stretching. On the other hand, the thermoplastic resin substrate preferably has a water absorption rate of about 3% or less, and more preferably about 1% or less, from the viewpoint of preventing problems such as a significant decrease in the dimensional stability of the thermoplastic resin substrate and deterioration of the appearance of the resulting polarizing film. The water absorption rate can be adjusted, for example, by introducing a modifying group into the constituent material of the thermoplastic resin substrate. The water absorption rate is a value determined in accordance with JIS K 7209.
[0059] From the viewpoint of ensuring sufficient stretchability of the laminate while suppressing crystallization of the PVA-based resin layer, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably about 120°C or lower. Furthermore, considering the plasticization of the thermoplastic resin substrate by water and good stretching in water, the glass transition temperature (Tg) is more preferably about 100°C or lower, and even more preferably about 90°C or lower. On the other hand, from the viewpoint of preventing defects such as deformation of the thermoplastic resin substrate when applying and drying the coating liquid, and producing a good laminate, the glass transition temperature of the thermoplastic resin substrate is preferably about 60°C or higher. The glass transition temperature can be adjusted, for example, by introducing a modifying group into the constituent material of the thermoplastic resin substrate or by heating with a crystallizing material. The glass transition temperature (Tg) is a value determined in accordance with JIS K 7121.
[0060] Any suitable thermoplastic resin can be used as the constituent material of the thermoplastic resin substrate. Examples of such thermoplastic resins include ester resins such as polyethylene terephthalate resins, cycloolefin resins such as norbornene resins, olefin resins such as polypropylene, polyamide resins, polycarbonate resins, and copolymer resins thereof. Among these, norbornene resins and amorphous polyethylene terephthalate resins are preferred, and furthermore, amorphous polyethylene terephthalate resins are preferably used from the viewpoint that the thermoplastic resin substrate has excellent stretchability and crystallization during stretching can be suppressed. Examples of amorphous polyethylene terephthalate resins include copolymers containing isophthalic acid and / or cyclohexanedicarboxylic acid as dicarboxylic acid, and copolymers containing cyclohexanedimethanol or diethylene glycol as glycol.
[0061] The thermoplastic resin substrate may be subjected to surface treatment (e.g., corona treatment) or an easy-adhesion layer may be formed on the thermoplastic resin substrate before the PVA-based resin layer is formed. By performing such treatments, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved. Furthermore, the thermoplastic resin substrate may be stretched before the PVA-based resin layer is formed.
[0062] The coating solution is a solution obtained by dissolving a PVA-based resin in a solvent. Examples of the solvent include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine, with water being preferred. These can be used alone or in combination of two or more. From the viewpoint of forming a uniform coating film that adheres closely to the thermoplastic resin substrate, the concentration of the PVA-based resin in the coating solution is preferably about 3 to 20 parts by weight per 100 parts by weight of solvent.
[0063] The coating solution preferably contains a halide to improve the orientation of polyvinyl alcohol molecules upon stretching. Any suitable halide can be used as the halide, for example, iodide and sodium chloride. Examples of iodides include potassium iodide, sodium iodide, and lithium iodide, with potassium iodide being preferred. The concentration of the halide in the coating solution is preferably about 5 to 20 parts by weight, and more preferably about 10 to 15 parts by weight, per 100 parts by weight of the PVA resin.
[0064] Furthermore, additives may be added to the coating solution. Examples of such additives include plasticizers such as ethylene glycol and glycerin; and surfactants such as nonionic surfactants.
[0065] Any suitable method can be used to apply the coating solution, such as roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.). Furthermore, the drying temperature of the coating solution is preferably 50°C or higher.
[0066] <Aerial Auxiliary Stretching Process> The aerial assisted stretching process allows for stretching of the thermoplastic resin substrate while suppressing crystallization, thereby enabling high-magnification stretching of the laminate. The stretching method in the aerial assisted stretching process may be fixed-end stretching (for example, stretching using a tenter stretcher) or free-end stretching (for example, uniaxial stretching by passing the laminate between rolls with different peripheral speeds), but free-end stretching is preferred from the viewpoint of obtaining high optical properties.
[0067] The stretching ratio in the aerial auxiliary stretching process is preferably about 2 to 3.5 times. The aerial auxiliary stretching process may be performed in one stage or in multiple stages. When performed in multiple stages, the stretching ratio is the product of the stretching ratios of each stage.
[0068] The stretching temperature in the aerial auxiliary stretching process can be set to any appropriate value depending on the forming material of the thermoplastic resin substrate, the stretching method, etc. For example, it is preferably above the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably above the glass transition temperature (Tg) + 10°C, and even more preferably above the glass transition temperature (Tg) + 15°C. On the other hand, the upper limit of the stretching temperature is preferably around 170°C from the viewpoint of suppressing the rapid crystallization of the PVA resin and suppressing defects caused by crystallization (for example, hindering the orientation of the PVA resin layer by stretching).
[0069] <Isolubilization process> If necessary, an insolubilization treatment step may be performed after the aerial assisted stretching treatment step and before the dyeing treatment step or the underwater stretching treatment step. The insolubilization treatment step is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. By performing the insolubilization treatment step, water resistance can be imparted to the PVA-based resin layer, and a decrease in the orientation of PVA when immersed in water can be prevented. The concentration of the aqueous boric acid solution is preferably about 1 to 5 parts by weight per 100 parts by weight of water. The liquid temperature of the insolubilization treatment bath is preferably about 20 to 50°C.
[0070] <Dyeing Process> The aforementioned dyeing process is carried out by dyeing the PVA-based resin layer with iodine. Examples of adsorption methods include immersing the PVA-based resin layer (laminated) in a dyeing solution containing iodine, coating the PVA-based resin layer with the dyeing solution, and spraying the dyeing solution onto the PVA-based resin layer. The method of immersing the PVA-based resin layer (laminated) in a dyeing solution containing iodine is preferred.
[0071] The amount of iodine in the dyeing bath is preferably about 0.05 to 0.5 parts by weight per 100 parts by weight of water. To increase the solubility of iodine in water, it is preferable to add the iodide to the iodine aqueous solution. The amount of iodide added is preferably about 0.1 to 10 parts by weight, and more preferably about 0.3 to 5 parts by weight, per 100 parts by weight of water. The liquid temperature of the dyeing bath is preferably about 20 to 50°C to suppress the dissolution of the PVA resin. The immersion time is preferably about 5 seconds to 5 minutes, and more preferably about 30 seconds to 90 seconds, from the viewpoint of ensuring the transmittance of the PVA resin layer. From the viewpoint of obtaining a polarizing film with good optical properties, the ratio of iodine to iodide content in the iodine aqueous solution is preferably about 1:5 to 1:20, and more preferably about 1:5 to 1:10.
[0072] <Cross-linking process> If necessary, a crosslinking treatment may be performed after the dyeing treatment step and before the underwater stretching treatment step. Typically, the crosslinking treatment is performed by immersing the PVA-based resin layer in an aqueous boric acid solution. By performing the crosslinking treatment, water resistance is imparted to the PVA-based resin layer, and a decrease in the orientation of PVA when immersed in high-temperature water during subsequent underwater stretching can be prevented. The boric acid concentration of the aqueous boric acid solution is preferably about 1 to 5 parts by weight per 100 parts by weight of water. Furthermore, when performing the crosslinking treatment, it is preferable to further add the iodide to the crosslinking bath. By adding the iodide, the elution of iodine adsorbed on the PVA-based resin layer can be suppressed. The amount of iodide added is preferably about 1 to 5 parts by weight per 100 parts by weight of water. The liquid temperature of the crosslinking bath (aqueous boric acid solution) is preferably about 20 to 50°C.
[0073] <Underwater stretching process> The underwater stretching process is carried out by immersing the laminate in a stretching bath. The underwater stretching process allows stretching at a temperature lower than the glass transition temperature (typically around 80°C) of the thermoplastic resin substrate or the PVA-based resin layer, and enables high-magnification stretching of the PVA-based resin layer while suppressing its crystallization. The stretching method in the underwater stretching process may be fixed-end stretching (for example, stretching using a tenter stretcher) or free-end stretching (for example, uniaxial stretching by passing the laminate between rolls with different peripheral speeds), but free-end stretching is preferred from the viewpoint of obtaining high optical properties.
[0074] The aforementioned underwater stretching process is preferably carried out by immersing the laminate in an aqueous boric acid solution (boric acid underwater stretching). By using an aqueous boric acid solution as the stretching bath, the PVA resin layer can be given rigidity to withstand the tension applied during stretching and water resistance that prevents it from dissolving in water. The boric acid concentration of the aqueous boric acid solution is preferably 1 to 10 parts by weight, and more preferably 2.5 to 6 parts by weight, per 100 parts by weight of water. Iodide may also be added to the stretching bath (aqueous boric acid solution). The liquid temperature of the stretching bath is preferably around 40 to 85°C, and more preferably around 60 to 75°C. The immersion time of the laminate in the stretching bath is preferably around 15 seconds to 5 minutes.
[0075] The stretching ratio in the underwater stretching process is preferably about 1.5 times or more, and more preferably about 3 times or more.
[0076] Furthermore, the total stretching ratio of the laminate is preferably about 5 times or more, and more preferably about 5.5 times or more, relative to the original length of the laminate.
[0077] <Cleaning Process> It is preferable to perform a washing process after the underwater stretching process. Typically, the washing process is carried out by immersing the PVA-based resin layer in an aqueous potassium iodide solution.
[0078] Furthermore, each treatment bath in the dyeing treatment step, the underwater stretching treatment step, the immobilization treatment step, the crosslinking treatment step, and the washing treatment step may contain additives such as zinc salts, pH adjusters, pH buffers, and other salts. Examples of zinc salts include zinc halides such as zinc chloride and zinc iodide; and inorganic zinc salts such as zinc sulfate and zinc acetate. Examples of pH adjusters include strong acids such as hydrochloric acid, sulfuric acid, and nitric acid, and strong bases such as sodium hydroxide and potassium hydroxide. Examples of pH buffers include carboxylic acids and their salts such as acetic acid, oxalic acid, and citric acid, and inorganic weak acids and their salts such as phosphoric acid and carbonic acid. Examples of other salts include chlorides such as sodium chloride, potassium chloride, and barium chloride; nitrates such as sodium nitrate and potassium nitrate; sulfates such as sodium sulfate and potassium sulfate; and salts of alkali metals and alkaline earth metals.
[0079] <Transparent protective film> The transparent protective film is not particularly limited, and various transparent protective films used in polarizing films can be used. As the material constituting the transparent protective film, for example, a thermoplastic resin that is excellent in transparency, mechanical strength, thermal stability, moisture barrier properties, isotropy, etc., can be used. Examples of the thermoplastic resin include cellulose ester resins such as triacetylcellulose, polyester resins such as polyethylene terephthalate and polyethylene naphthalate, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins such as nylon and aromatic polyamides, polyimide resins, polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers, (meth)acrylic resins, cyclic polyolefin resins having a cyclo or norbornene structure (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. Furthermore, the transparent protective film can be a cured layer formed from thermosetting resins such as (meth)acrylic, urethane, acrylic urethane, epoxy, and silicone resins, or UV-curable resins. Among these, cellulose ester resins, polycarbonate resins, (meth)acrylic resins, cyclic polyolefin resins, and polyester resins are preferred.
[0080] The thickness of the transparent protective film can be determined as appropriate, but generally, from the viewpoint of strength, workability such as handling, and thinness, it is preferably about 1 to 500 μm, more preferably about 1 to 300 μm, and even more preferably about 5 to 100 μm.
[0081] When the transparent protective film is laminated to both sides of the polarizing film, the transparent protective films on both sides may be the same or different.
[0082] The transparent protective film can use a phase difference plate having a front phase difference of 40 nm or more and / or a thickness direction phase difference of 80 nm or more. The front phase difference is usually controlled in the range of 40 to 200 nm, and the thickness direction phase difference is usually controlled in the range of 80 to 300 nm. When a phase difference plate is used as the transparent protective film, the phase difference plate also functions as the transparent protective film, thus enabling a thinner design.
[0083] Examples of the phase difference plate include a birefringent film obtained by uniaxial or biaxial stretching of a polymer material, an orientation film of a liquid crystal polymer, and a liquid crystal polymer orientation layer supported by a film. The thickness of the phase difference plate is not particularly limited, but it is generally around 20 to 150 μm. The phase difference plate may also be used by laminating it to a transparent protective film that does not have a phase difference.
[0084] The transparent protective film may contain any suitable additives such as ultraviolet absorbers, antioxidants, lubricants, plasticizers, mold release agents, color inhibitors, flame retardants, antistatic agents, pigments, and colorants. In particular, if the transparent protective film contains an ultraviolet absorber, the light resistance of the polarizing film can be improved.
[0085] Functional layers such as a hard coat layer, anti-reflective layer, anti-sticking layer, diffusion layer, or anti-glare layer can be provided on the surface of the transparent protective film that does not have a polarizing film bonded to it. These functional layers can be provided on the protective film itself, or they can be provided separately from the protective film.
[0086] The polarizing film and the transparent protective film, or the polarizing film and the functional layer, are usually bonded together via an adhesive layer or bonding agent.
[0087] Various adhesives used in polarizing films can be applied as the adhesive forming the aforementioned adhesive layer. Examples include rubber-based adhesives, acrylic-based adhesives, silicone-based adhesives, urethane-based adhesives, vinyl alkyl ether-based adhesives, polyvinyl alcohol-based adhesives, polyvinyl polyoridone-based adhesives, polyacrylamide-based adhesives, and cellulose-based adhesives. Among these, acrylic-based adhesives are preferred.
[0088] Examples of methods for forming the adhesive layer include applying the adhesive to a peeled separator, drying it to form the adhesive layer, and then transferring it to a polarizing film, or applying the adhesive to a polarizing film and drying it to form the adhesive layer. The thickness of the adhesive layer is not particularly limited, but is preferably about 1 to 100 μm, and preferably about 2 to 50 μm.
[0089] Various adhesives used in polarizing films can be used as the adhesive for forming the adhesive layer, such as isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latex adhesives, and aqueous polyester adhesives. These adhesives are usually used as aqueous solutions (aqueous adhesives) and contain 0.5 to 60% by weight of solids. Among these, polyvinyl alcohol adhesives are preferred, and acetoacetyl group-containing polyvinyl alcohol adhesives are more preferred.
[0090] The water-based adhesive may contain a crosslinking agent. Typically, the crosslinking agent is a compound having at least two functional groups in one molecule that are reactive with the polymer and other components constituting the adhesive. Examples include alkylenediamines; isocyanates; epoxys; aldehydes; amino-formaldehydes such as methylolurea and methylolmelamine. The amount of crosslinking agent in the adhesive is typically about 10 to 60 parts by weight per 100 parts by weight of the polymer and other components constituting the adhesive.
[0091] In addition to the above, other adhesives include active energy ray curing adhesives such as ultraviolet curing adhesives and electron beam curing adhesives. Examples of active energy ray curing adhesives include (meth)acrylate adhesives. Examples of curable components in (meth)acrylate adhesives include compounds having a (meth)acryloyl group and compounds having a vinyl group. Examples of compounds having a (meth)acryloyl group include alkyl (meth)acrylates such as chain-like alkyl (meth)acrylates having 1 to 20 carbon atoms, alicyclic alkyl (meth)acrylates, and polycyclic alkyl (meth)acrylates; hydroxyl group-containing (meth)acrylates; and epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate. (Meth)acrylate adhesives may contain nitrogen-containing monomers such as hydroxyethyl (meth)acrylamide, N-methylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-ethoxymethyl (meth)acrylamide, (meth)acrylamide, and (meth)acryloylmorpholine. (Meth)acrylate adhesives may also contain polyfunctional monomers as crosslinking components, such as tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecanedimethanol diacrylate, cyclic trimethylolpropaneformal acrylate, dioxane glycol diacrylate, and EO-modified diglycerin tetraacrylate. Compounds having epoxy groups or oxetanyl groups can also be used as cationic polymerization-curable adhesives. Compounds having epoxy groups are not particularly limited as long as they have at least two epoxy groups in the molecule, and various generally known curable epoxy compounds can be used.
[0092] The adhesive may contain appropriate additives as needed. Examples of such additives include coupling agents such as silane coupling agents and titanium coupling agents, adhesion promoters such as ethylene oxide, ultraviolet absorbers, degradation inhibitors, dyes, processing aids, ion trapping agents, antioxidants, tackifiers, fillers, plasticizers, leveling agents, foam inhibitors, antistatic agents, heat stabilizers, hydrolysis stabilizers, and the like.
[0093] The adhesive may be applied to either the transparent protective film side (or the functional layer side), the polarizing film side, or both. After bonding, a drying process is performed to form an adhesive layer consisting of the applied and dried layer. After the drying process, ultraviolet light or electron beams may be irradiated as necessary. The thickness of the adhesive layer is not particularly limited, but when using a water-based adhesive, it is preferably about 30 to 5000 nm, more preferably about 100 to 1000 nm, and when using an ultraviolet-curing adhesive, electron beam-curing adhesive, etc., it is preferably about 0.1 to 100 μm, more preferably about 0.5 to 10 μm.
[0094] The transparent protective film and the polarizing film, or the polarizing film and the functional layer, may be laminated with an intervening layer such as a surface modification layer, an easy-adhesion layer, a block layer, or a refractive index adjustment layer.
[0095] Examples of surface modification treatments for forming the aforementioned surface modification layer include corona treatment, plasma treatment, primer treatment, and saponification treatment.
[0096] Examples of easy-to-adhere adhesives for forming the easy-to-adhere layer include forming materials containing various resins having a polyester skeleton, polyether skeleton, polycarbonate skeleton, polyurethane skeleton, silicone-based materials, polyamide skeleton, polyimide skeleton, polyvinyl alcohol skeleton, etc. The easy-to-adhere layer is usually provided in advance on a protective film, and the easy-to-adhere layer side of the protective film and the polarizing film are laminated together with the adhesive layer or the adhesive layer.
[0097] The aforementioned block layer is a layer that functions to prevent impurities such as oligomers and ions eluted from the transparent protective film, etc., from migrating (penetrating) into the polarizing film. The block layer only needs to be transparent and capable of preventing impurities eluted from the transparent protective film, etc. Examples of materials that form the block layer include urethane prepolymer-based forming materials, cyanoacrylate-based forming materials, epoxy-based forming materials, etc.
[0098] The refractive index adjusting layer is provided to suppress the decrease in transmittance due to reflection between layers with different refractive indices, such as the transparent protective film and the polarizing film. Examples of refractive index adjusting materials for forming the refractive index adjusting layer include various resins and additives such as silica-based, acrylic-based, acrylic-styrene-based, and melamine-based resins.
[0099] <Laminated polarizing film> The laminated polarizing film (optical laminate) of the present invention is characterized in that the polarizing film is laminated to an optical layer. The optical layer is not particularly limited, but for example, one or more optical layers that are used in the formation of liquid crystal display devices such as reflectors, semitransparent plates, phase difference plates (including 1 / 2 or 1 / 4 wave plates), and viewing angle compensation films can be used. In particular, examples of the laminated polarizing film include a reflective polarizing film or a semitransparent polarizing film in which a reflector or semitransparent reflector is further laminated on the polarizing film, an elliptical polarizing film or a circular polarizing film in which a phase difference plate is further laminated on the polarizing film, a wide viewing angle polarizing film in which a viewing angle compensation film is further laminated on the polarizing film, or a polarizing film in which a brightness enhancement film is further laminated on the polarizing film.
[0100] An adhesive layer may be provided on one or both sides of the polarizing film, or the laminated polarizing film, for bonding an image display cell such as a liquid crystal cell or an organic EL element to another component such as a transparent front plate or touch panel on the viewing side. A tack layer is preferred as the adhesive layer. The tack forming the tack layer is not particularly limited, but for example, acrylic polymers, silicone polymers, polyesters, polyurethanes, polyamides, polyethers, fluorine-based polymers, rubber-based polymers, etc., can be appropriately selected and used. In particular, tacks containing acrylic polymers are preferred because they have excellent optical transparency, exhibit appropriate wettability, cohesiveness and adhesion, and have excellent weather resistance and heat resistance.
[0101] The adhesive layer can be attached to one or both sides of the polarizing film or the laminated polarizing film by any suitable method. Examples of methods for attaching the adhesive layer include preparing an adhesive solution and directly attaching it to the polarizing film or the laminated polarizing film by any suitable application method such as casting or coating, or forming an adhesive layer on a separator and transferring it to the polarizing film or the laminated polarizing film. The thickness of the adhesive layer can be appropriately determined according to the intended use and adhesive strength, and is generally 1 to 500 μm, preferably 5 to 200 μm, and more preferably 10 to 100 μm. A polarizing film or laminated polarizing film with an adhesive layer on at least one side is called a polarizing film with an adhesive layer or a laminated polarizing film with an adhesive layer.
[0102] It is preferable that a separator be temporarily attached to the exposed surface of the adhesive layer to prevent contamination until it is put into practical use. This prevents contamination of the adhesive layer under normal handling conditions. As the separator, for example, a suitable thin sheet such as a plastic film, rubber sheet, paper, cloth, nonwoven fabric, net, foam sheet, metal foil, or laminate thereof may be used, and may be coated with a suitable release agent such as silicone-based, long-chain alkyl-based, fluorine-based, or molybdenum sulfide as needed.
[0103] <Image display panel and image display device> The image display panel of the present invention has the polarizing film or the laminated polarizing film laminated onto an image display cell. Furthermore, the image display device of the present invention is provided with a front transparent member on the polarizing film or laminated polarizing film side (viewing side) of the image display panel.
[0104] Examples of the image display cell include liquid crystal cells and organic EL cells. The liquid crystal cell may be a reflective liquid crystal cell that utilizes ambient light, a transmissive liquid crystal cell that utilizes light from a backlight or other light source, or a semi-transparent, semi-reflective liquid crystal cell that utilizes both ambient light and light from a light source. If the liquid crystal cell utilizes light from a light source, the image display device (liquid crystal display device) also has a polarizing film on the side opposite to the viewing side of the image display cell (liquid crystal cell), and a light source is further positioned therein. Preferably, the polarizing film on the light source side and the liquid crystal cell are bonded together via an appropriate adhesive layer. As for the driving method of the liquid crystal cell, any type may be used, such as VA mode, IPS mode, TN mode, STN mode, or bend orientation (π type).
[0105] As the organic EL cell, for example, one in which a light-emitting body (organic electroluminescent light-emitting body) is formed by sequentially laminating a transparent electrode, an organic light-emitting layer, and a metal electrode on a transparent substrate is preferably used. The organic light-emitting layer is a laminate of various organic thin films, and various layer configurations can be adopted, such as a laminate of a hole injection layer made of a triphenylamine derivative or the like and a light-emitting layer made of a fluorescent organic solid such as anthracene, a laminate of these light-emitting layers and an electron injection layer made of a perylene derivative or the like, or a laminate of a hole injection layer, a light-emitting layer and an electron injection layer.
[0106] Examples of front transparent members positioned on the viewing side of the image display cell include a front transparent plate (window layer) and a touch panel. The front transparent plate is a transparent plate having appropriate mechanical strength and thickness. Examples of such transparent plates include transparent resin plates such as acrylic resin and polycarbonate resin, or glass plates. The touch panel is a variety of touch panels such as resistive, capacitive, optical, and ultrasonic types, or a glass plate or transparent resin plate equipped with a touch sensor function. When a capacitive touch panel is used as the front transparent member, it is preferable to provide a front transparent plate made of glass or a transparent resin plate further on the viewing side than the touch panel. [Examples]
[0107] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0108] <Example 1> <Fabrication of polarizing films> A polyvinyl alcohol film with an average degree of polymerization of 2,400, a degree of saponification of 99.9 mol%, and a thickness of 45 μm was prepared. The polyvinyl alcohol film was immersed in a 20°C swelling bath (water bath) for 30 seconds between rolls with different peripheral speed ratios to swell and stretched to 2.2 times its original size in the transport direction (swelling process). Subsequently, it was immersed in a 30°C dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) for 30 seconds, adjusting the concentration so that the final polarizing film would have an iodine concentration of 3.0% by weight, and dyed while being stretched to 3.3 times its original size in the transport direction, relative to the original polyvinyl alcohol film (a polyvinyl alcohol film that had not been stretched at all in the transport direction) (dyeing process). Next, the dyed polyvinyl alcohol film was immersed for 28 seconds in a 40°C crosslinking bath (an aqueous solution with a boric acid concentration of 3.5 wt%, a potassium iodide concentration of 3.0 wt%, and a zinc sulfate concentration of 3.6 wt%) to stretch it to 3.6 times its original size in the transport direction (crosslinking step). Furthermore, the resulting polyvinyl alcohol film was immersed for 60 seconds in a 64°C stretching bath (an aqueous solution with a boric acid concentration of 4.5 wt%, a potassium iodide concentration of 5.0 wt%, and a zinc sulfate concentration of 5.0 wt%) to stretch it to 6.0 times its original size in the transport direction (stretching step). After that, it was immersed for 10 seconds in a 27°C washing bath (an aqueous solution with a potassium iodide concentration of 2.3 wt% and a water-soluble radical scavenging agent with a concentration of 1.0 wt% of the compound represented by the following general formula (9)) (washing step). The washed polyvinyl alcohol film was dried at 40°C for 30 seconds to produce a polarizing film. The iodine concentration of the polarizing film was determined by the following measurement method. The content of the compound represented by the following general formula (9) in the polarizing film was 0.3% by weight, and the thickness of the polarizing film was 18 μm. The compound represented by the following general formula (9) is a compound that dissolves at a rate of 1 part by weight or more in 100 parts by weight of water at 25°C. [C9]
[0109] [Method for measuring iodine concentration (weight %) in polarizing films] The iodine concentration (by weight) of the polarizing film was determined using a fluorescence X-ray analyzer (Rigaku Corporation, product name "ZSX-PRIMUS IV", measurement diameter: ψ20 mm) and the following formula. Iodine concentration (wt%) = 14.474 × (fluorescent X-ray intensity) / (film thickness) (kcps / μm). Note that the coefficient used to calculate the concentration varies depending on the measuring device, but this coefficient can be determined using an appropriate calibration curve.
[0110] [Method for measuring the content (by weight) of water-soluble radical scavenger in polarizing films] Approximately 20 mg of polarizing film was collected and quantified. It was then heated and dissolved in 1 mL of water, diluted with 4.5 mL of methanol, and the resulting extract was filtered through a membrane filter. The concentration of the water-soluble radical scavenger in the filtrate was measured using HPLC (Waters ACQUITY UPLC H-class Bio).
[0111] <Preparation of polarizing film> As an adhesive, an aqueous solution containing polyvinyl alcohol resin containing acetoacetyl groups (average degree of polymerization 1,200, degree of saponification 98.5 mol%, degree of acetoacetylation 5 mol%) and methylolmelamine in a weight ratio of 3:1 was used. Using this adhesive, a 30 μm thick transparent protective film made of (meth)acrylic resin (modified acrylic polymer having a lactone ring structure) (manufactured by Nippon Shokubai, with a moisture permeability of 125 g / m²) was applied to one side (image display device cell side) of the polarizing film obtained above. 2 A polarizing film was created by laminating a 49 μm thick transparent protective film (moisture permeability of 300 g / (m2·24h)) with HC formed on a triacetylcellulose film (manufactured by Fujifilm, product name "TJ40UL") to the other side (visibility side) using a roll laminating machine, and then heating and drying it in an oven (temperature 90°C, time 10 minutes) to produce a polarizing film in which transparent protective films were laminated to both sides of the polarizing film.
[0112] <Preparation of acrylic adhesive> A monomer mixture containing 99 parts butyl acrylate and 1 part 4-hydroxybutyl acrylate was charged into a four-necked flask equipped with a stirring blade, thermometer, nitrogen gas inlet tube, and condenser. Furthermore, 0.1 parts 2,2'-azobisisobutyronitrile was added as a polymerization initiator to 100 parts of the monomer mixture (solid content) along with 100 parts ethyl acetate. After introducing nitrogen gas and purging the mixture with nitrogen while gently stirring, the polymerization reaction was carried out for 8 hours while maintaining the liquid temperature in the flask at around 55°C to prepare a solution of an acrylic polymer with a weight-average molecular weight (Mw) of 1.8 million. Subsequently, to 100 parts of the solid content of the obtained acrylic polymer solution, 0.02 parts of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "Takenate D110N", trimethylolpropane / xylylene diisocyanate adduct) and 0.2 parts of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "X-41-1056") were added to prepare an acrylic adhesive composition solution. Next, the acrylic adhesive composition solution obtained above was applied to one side of a polyethylene terephthalate film (manufactured by Mitsubishi Chemical Polyester Films, trade name "MRF38", separator film) treated with a silicone release agent, so that the thickness of the adhesive layer after drying would be 20 μm, and dried at 90°C for 1 minute to form an adhesive layer on the surface of the separator film. Next, the adhesive layer formed on the separator film was transferred to one side of the polarizing film prepared above to produce a polarizing film with an adhesive layer.
[0113] [Evaluation of changes in individual unit transmittance under high-temperature environments] The polarizing film with adhesive layer obtained above was cut to a size of 300 × 100 mm so that the absorption axis of the polarizing film was on the longer side. A glass plate (pseudo-image display cell) was bonded to the film via the adhesive layer, and a laminate sample was prepared by autoclaving at 50°C and 0.5 MPa for 15 minutes. The resulting laminate was left to stand in a hot air oven at 105°C for 1000 hours, and the transmittance of the individual components (ΔTs) before and after heating was measured. The transmittance of the individual components was measured using a spectrophotometer (JASCO Corporation, product name "V7100") and evaluated according to the following criteria. The measurement wavelength was 380 to 700 nm (in 5 nm increments). The results are shown in Table 1. ΔTs(%)=Ts 1000 -Ts0 Here, Ts0 is the transmittance of the laminate before heating, and Ts 1000 This represents the transmittance of a single laminate after heating for 1000 hours.
[0114] The aforementioned ΔTs(%) is preferably 5≧ΔTs(%)≧0, and more preferably 3≧ΔTs(%)≧0.
[0115] [Evaluation of transverse crack formation parallel to the absorption axis of polarizing films under high-temperature conditions] The laminate samples described above were left standing in a hot air oven at 105°C for 1000 hours, then removed in a cleanroom set to 23°C and 55% relative humidity. After 10 minutes, the appearance was visually evaluated according to the following criteria. ○: No transverse cracks occurred in the polarizing film parallel to the absorption axis. ×: Transverse cracks have occurred in the polarizing film, parallel to the absorption axis.
[0116] <Example 2> A laminate was fabricated using the same procedure as in Example 1, except that a polarizing film with an adhesive layer was cut to a size of 850 x 300 mm such that the absorption axis of the polarizing film was on the longer side, and a glass plate (pseudo-image display cell) was bonded to it via the adhesive layer.
[0117] <Example 3> A laminate was fabricated using the same procedure as in Example 1, except that a polarizing film with an adhesive layer was cut to a size of 440 x 115 mm such that the absorption axis of the polarizing film was on the longer side, and a glass plate (pseudo-image display cell) was bonded to it via the adhesive layer.
[0118] <Example 4> In the preparation of the polarizing film, a polyvinyl alcohol film with a thickness of 30 μm was prepared, and the laminate was fabricated using the same procedure as in Example 1, except that the iodine concentration of the final polarizing film was 4.2% by weight. The content of the compound represented by the above general formula (9) in the polarizing film was 0.3% by weight, and the thickness of the polarizing film was 12 μm.
[0119] <Example 5> A laminate was fabricated using the same procedure as in Example 1, except that a polarizing film with an adhesive layer was cut to a size of 680 x 80 mm such that the absorption axis of the polarizing film was on the longer side, and a glass plate (pseudo-image display cell) was bonded to it via the adhesive layer.
[0120] <Example 6> A laminate was fabricated using the same procedure as in Example 4, except that a polarizing film with an adhesive layer was cut to a size of 1260 x 300 mm such that the absorption axis of the polarizing film was on the longer side, and a glass plate (pseudo-image display cell) was bonded to it via the adhesive layer.
[0121] <Example 7> In the preparation of the polarizing film, a polyvinyl alcohol film with a thickness of 20 μm was prepared, and the iodine concentration of the final polarizing film was set to 5.4% by weight. In the washing process, the film was immersed for 10 seconds in an 18°C washing bath (an aqueous solution with a potassium iodide concentration of 3.6% by weight and a compound represented by the general formula (9) below as a water-soluble radical scavenger in an aqueous solution) for 10 seconds. The content of the compound represented by the general formula (9) above in the polarizing film was 0.3% by weight, and the thickness of the polarizing film was 7 μm.
[0122] <Comparative Example 1> In the preparation of the polarizing film, the laminate was fabricated using the same procedure as in Example 1, except that the above general formula (9) was not added to the washing bath as a water-soluble radical scavenger.
[0123] <Comparative Example 2> In the preparation of the polarizing film, the laminate was fabricated using the same procedure as in Example 2, except that the above general formula (9) was not added to the washing bath as a water-soluble radical scavenger.
[0124] The above evaluations were performed using the laminates of the examples and comparative examples obtained above. The results are shown in Table 1.
[0125] [Table 1]
Claims
1. A polarizing film in which a transparent protective film is attached to one or both sides of a polarizing film, the polarizing film contains a water-soluble radical scavenger; and General formula (X): 2.0≦a / b A polarizing film characterized by satisfying the length ratio condition represented by the general formula (X): (in general formula (X), a represents the length (mm) parallel to the absorption axis of the polarizing film and is a value greater than 200, and b represents the length (mm) perpendicular to the absorption axis of the polarizing film).
2. 2. The polarizing film according to claim 1, wherein the polarizing film has a thickness of 4 to 20 μm.
3. 3. The polarizing film according to claim 1, wherein the water-soluble radical scavenger is a compound having a nitroxy radical or a nitroxide group.
4. A laminated polarizing film, comprising the polarizing film according to any one of claims 1 to 3 laminated to an optical layer.
5. 10. An image display panel comprising an image display cell to which the polarizing film according to claim 1 or the laminated polarizing film according to claim 4 is attached.
6. 6. An image display device comprising: a front transparent member on the polarizing film or laminated polarizing film side of the image display panel according to claim 5.